Attitudes of medicine, pharmacy, and dentistry students about psychostimulant use to enhance cognition - (:unkn) unknown (WILEY, 2022)
Introduction The use of psychostimulant drugs to increase academic success is common among young people. There is no study examining this issue in Turkish population. In this study, the prevalence, attitudes, knowledge, and ethical evaluations of Pharmacological Cognitive Enhancement (PCE) in university students were investigated. Method A structured online survey was carried out with 1148 undergraduate and postgraduate (master, PhD and residency) students in different faculties of Medicine, Dentistry and Pharmacy in Turkey. Comparisons between groups, correlation and regression analysis about associated variables were made. Results The general prevalence of PCE in our study was found to be 7.4%. The highest prevalence was seen in the faculty of medicine (8.4%), among the residency students (15.5%). There was no significant difference prevalence of PCE between the faculties. Education level, smoking, study performance satisfaction, and knowledge level were found to be factors associated with PCE. Around 40% of PCE users stated that they used it with the recommendation of their friends. PCE users had a lower perception of harm and risk, and rated the use of it as more acceptable and normal behaviour. Conclusion PCE is a method used by young with high knowledge, low study performance satisfaction, to increase their academic success, especially during exam periods. Peer effect is an important factor in increasing prevalence.
Keywords: PRESCRIPTION STIMULANTS; NONMEDICAL USE; COLLEGE-STUDENTS; ILLICIT USE; MISUSE; MEDICATIONS; PREVALENCE; MOTIVES